Feasibility of real‐time motion management with helical tomotherapy. Issue 4 (23rd February 2018) - Schnarr, Eric; Beneke, Matt; Casey, Dylan; Chao, Edward; Chappelow, Jonathan; Cox, Andrea; Henderson, Doug; Jordan, Petr; Lessard, Etienne; Lucas, Dan; Myronenko, Andriy; Maurer, Calvin
Abstract : Purpose: This study investigates the potential application of image‐based motion tracking and real‐time motion correction to a helical tomotherapy system. Methods: A kV x‐ray imaging system was added to a helical tomotherapy system, mounted 90 degrees offset from the MV treatment beam, and an optical camera system was mounted above the foot of the couch. This experimental system tracks target motion by acquiring an x‐ray image every few seconds during gantry rotation. For respiratory (periodic) motion, software correlates internal target positions visible in the x‐ray images with marker positions detected continuously by the camera, and generates an internal–external correlation model to continuously determine the target position in three‐dimensions (3D). Motion correction is performed by continuously updating jaw positions and MLC leaf patterns to reshape (effectively re‐pointing) the treatment beam to follow the 3D target motion. For motion due to processes other than respiration (e.g., digestion), no correlation model is used — instead, target tracking is achieved with the periodically acquired x‐ray images, without correlating with a continuous camera signal. Results: The system's ability to correct for respiratory motion was demonstrated using a helical treatment plan delivered to a small (10 mm diameter) target. The phantom was moved following a breathing trace with an amplitude of 15 mm. Film measurements of delivered dose without motion, with motion, and with motion correction were acquired. Without motion correction, dose differences within the target of up to 30% were observed. With motion correction enabled, dose differences in the moving target were less than 2%. Nonrespiratory system performance was demonstrated using a helical treatment plan for a 55 mm diameter target following a prostate motion trace with up to 14 mm of motion. Without motion correction, dose differences up to 16% and shifts of greater than 5 mm were observed. Motion correction reduced these to less than a 6% dose difference and shifts of less than 2 mm. Conclusions: Real‐time motion tracking and correction is technically feasible on a helical tomotherapy system. In one experiment, dose differences due to respiratory motion were greatly reduced. Dose differences due to nonrespiratory motion were also reduced, although not as much as in the respiratory case due to less frequent tracking updates. In both cases, beam‐on time was not increased by motion correction, since the system tracks and corrects for motion simultaneously with treatment delivery.